Spory kompetencyjne związane z nadzorem bankowym - Frysztak, Małgorzata (Kwartalnik Prawa Publicznego, 2015)
This study takes up an issue from public banking law, and specifically the dispute between the Minister of the Treasury and the state authority that supervises the financial market (including banks). One of the difficult issues in banking practice is supervision, and especially the relations between supervisor and supervised. In this context, one of the problems that has emerged in recent years in connection with privatization agreements is the relation between banking supervision and other state institutions. Due to improper execution of bank privatization agreements, the Minister of the Treasury requested the Commission for Banking Supervision (now the Polish Financial Supervision Authority) to take necessary supervisory measures. However, the Minister’s attempt encountered a legitimate negative response from the supervising authority. The article explains why the supervisory body cannot act in the manner required by the Minister, and suggests that the problems connected with bank privatization can be solved by the State Treasury in civil proceedings (through such sanctions as relative ineffectiveness of the agreement, invalidity of legal action, or compensation). Disputes related to agreements between banks and the State Treasury, represented by the Minister of the Treasury, are subject to civil law, so in the case in question, the use of administrative law measures is unjustified. In view of the ongoing relevance of the problem, the fact that so far it has not been analyzed in subject literature gives this study an unprecedented character.